1982
DOI: 10.1007/bf00364261
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies as a tool for phylogenetic studies of major histocompatibility antigens and ? 2-microglobulin

Abstract: The cross-reactivity of several monoclonal antibodies recognizing monomorphic determinants of human HLA-A, B, C, and DR antigens and human beta 2-microglobulin (beta 2m) has been studied on peripheral blood leukocytes in 24 different species. An monoclonal HLA-A-, B-, and C-specific antibody and four monoclonal HLA-DR-specific antibodies cross-reacted with cells from all the primate species tested. Furthermore, antibodies HLA-DR-specific were positive with peripheral blood leukocytes (PBL) from cows, goats, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…mAb w6/32 (IgG2a) defines a monomorphic determinant on human HLA-A, -B, and -C molecules (21) and crossreacts in a nonpolymorphic fashion with bovine class I MHC molecules (22). mAb B1.1G6 (IgG2a) reacts with human and bovine P2-microglobulin (23,24). mAb BT3/8 (IgG2a) recognizes a cell surface molecule that is expressed on all cell lines infected with Theileria and on some normal bovine leukocytes (25).…”
Section: Methodsmentioning
confidence: 99%
“…mAb w6/32 (IgG2a) defines a monomorphic determinant on human HLA-A, -B, and -C molecules (21) and crossreacts in a nonpolymorphic fashion with bovine class I MHC molecules (22). mAb B1.1G6 (IgG2a) reacts with human and bovine P2-microglobulin (23,24). mAb BT3/8 (IgG2a) recognizes a cell surface molecule that is expressed on all cell lines infected with Theileria and on some normal bovine leukocytes (25).…”
Section: Methodsmentioning
confidence: 99%
“…In immunological studies, urinary β 2 -m cross-reacted with colostral β 2 -m, but not with human urinary β 2 -m. An investigation using monoclonal antibody against human β 2 -m revealed that a half of the antibodies did not react with bovine β 2 -m [28]. These findings indicate that bovine β 2 -m is not homologous to those of human β 2 -m in the epitope structure.…”
Section: Purification Of Bovine Urinary β 2 -M: Sds-page Patterns Ofmentioning
confidence: 87%
“…We also tested the effects of 2 anti-p2m mAb, M18 [28] and BBMl [29], and found that these mAb fully blocked [3H]dThd incorporation by whole PBL cultivated with the several CD3 mAb we tested (Table 1). However, we observed no blocking effects when whole PBL were cultivated with mitogenic pairs of CD2 mAb, including GT2 + T l l l (Table 1).…”
Section: Anti-pgn Mab Fured To Ac Inhibit T Cell Activation Via Cd3mentioning
confidence: 96%
“…Anti-HLA class I mAb directed against the heavy chain were W6132 (IgG,) [26], B10.8 (IgG3) [27], B10.22 (IgG3) [27] and B1.23.2 (IgG2,). Anti-p2-microglobulin (P2m) mAb were M18 (IgG,,) [28] and BBMl (IgGZb) [29]. In some experiments we used Fab or F(ab'), fragments of W6/32 mAb prepared, respectively, with a papain or pepsin digestion of purified mAb, and recovered by high performance liquid chromatography (HPLC) as described [30].…”
Section: Mabmentioning
confidence: 99%